The Effectiveness of Critical Thinking in Learning Christian Education - Julita Herawati P (Universitas Muhammadiyah Mataram, 2021)
The purpose of this study was to determine the effect of the effectiveness of critical thinking in teaching PAK for Class IX students of SMP. Motivation is needed by students to improve student learning outcomes. In this case the teacher plays an important role in motivating students. Great teachers are teachers who are able to arouse students' enthusiasm for learning. This description provides an overview of the importance of classroom management skills and providing student learning motivation, especially learning Christian Religious Education as a guide in forming students who have Christian values. This is a quantitative research and population in this study were all 200 students of Class IX in 2017. Samples were taken randomly (random sampling) of 50% of the total population, namely 100 people. The research data were analyzed in the following steps: 1) Test the analysis requirements obtained: a) rcount = 6.14> rtable (α = 0.05, CI = 95%, n = 32) = 2.00 thus it is known that there is a relationship positive b) The value of t = 6.14> ttable (α = 0.05, dk = 30) = 2.00 thus it is known that there is a significant relationship 2) The regression test obtained: a) regression equation: = 52.39 + 0.4X. This regression equation shows that in a constant state = 52.39, for every addition of one unit of variable X (PAK Lessons), there will be an addition of variable Y (Effectiveness of Critical Thinking) of 0.4. b) The regression coefficient test (r2) obtained r2 = 0.6399 and the percentage of influence between PAK Lessons on the Effectiveness of Critical Thinking was 63.99%. 3) Hypothesis testing with Simple Linear Regression Variance Analysis obtained the value of Fcount = 174.22> Ftabel (α = 0.05, dk = 30) = 4.00.